(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
International Accounting Standards achieved widespread have become as a sample of high-quality accounting standards . The application of accounting standards result in high-quality financial reports which are regarded as the main factor in determining the quality of these financial reports . International accounting standards are like any other set of standards which allow with some freedom to choose accounting policies that show the problem of the research through several questions: do the international accounting standards contribute to the development of the quality of accounting information? and what is its impact on the Iraqi environment? As the objective of the research is to shed light on international accounting, the research is based on the hypothesis that the accounting standards contributed to the improvement of the quality of accounting information. The researcher concluded several points: the most importantly is that : (through the analysis of the questionnaire, the dominant part of it calling for the application of international accounting standards in improving the quality of accounting information and the extent of its impact on the Iraqi environment after obtaining modification and adaptation of these international standards with the Iraqi environment. The most important recommendations the researcher gives are : the necessity of the participation in establishing a board of accounting and auditing standards in Iraq through issuing local standards that are in line with those of international ones to fill the large gap between the Iraqi standards and the international ones